Proteomics of rat biological fluids - The tenth anniversary update - Gianazza, E; Wait, R; Eberini, I; Sensi, C; Sironi, L; Miller, I (2012)
In addition to a remarkable sexual dimorphism of serum and urine proteomes, the rat is exceptional for the wide difference between the serum patterns during an acute phase reaction vs baseline conditions. This feature allows monitoring with high sensitivity onset and progression of any pathological state that involves an inflammatory component as well as assessing the outcome of any therapeutic intervention.Reference maps have been defined for the proteomes of serum, urine, cerebrospinal fluid and bronchoalveolar lavage fluid. For both serum and urine most of the proteomic investigations have dealt with toxicological testing, for BALF with allergic or irritative reactions, whereas with CSF the main aim was the characterization of rat models of neurological disorders.When surveying more than ten years of literature on rat biological fluid proteomics, it is puzzling to see how seldom a consistent analytical plan has been set up for the comparative investigation on two or more types of sample, whether to fully characterize a disease model or to evaluate pharmacological/toxicological effects of a drug. It is also regrettable that in several cases only a negligible part of the results is discussed at length whereas most data are not even made known to the scientific community. © 2012 Elsevier B.V.